Pembuatan Game 2D Petualangan Hanoman Berbasis Android - Toni Ardyanto; Anton Respati Pamungkas (Go Infotech: Jurnal Ilmiah STMIK AUB, 2017)
Game is one of the entertainment that is loved by a wide variety of backgrounds ranging from children to adults.  According to App Annie one type of game that is much in demand to play is a adventure game genre. Selected as entertainment because the game is able to reduce the fatigue of someone from the daily routine and spend a leisure time. The amount of smartphones user, especially  android-based  smartphones  in  daily  activities  cause  android-based  game  are  currently  popular  in  the  community. From these situation, author tries to make an adventure game genre based on Android. This game can be used as an option to eliminate  fatigue or just  fill emptiness in spare time by playing games, and also to encourage the establishment of  local game developers, which is still smal compared with the foreign game developers. Design of game is made from a storyboard and then designed the depiction of the character, background and obstacles using Adobe Illustrator CS 6. The completed game depictions of supporting element then applied to Unity Game Engine and built using C# programming language. The result of this research have produced a game called “The Adventure of  Hanuman” in 2D display Android-based. This game is played by one person and has three levels of obstacle. This game is adventure game genre.